Compensation in the Termination of Agreement Due to Breach of Contract - Al Hafiz, M.; Sukirno, Sukirno (STKIP Singkawang, 2024)
In the execution of an agreement, there are cases where parties are unable to fulfil their rights and obligations as agreed, resulting in a breach of contract, known as